Psychological analysis of emotional burnout among students of humanities - Semerenko, Y.; Prykhodko, Dmytro (ХДАК, 2025)
In the current context, emotional burnout among students of humanities is intensified by the combination of highly empathic academic interaction and prolonged stress factors of wartime: air raid alerts, power outages, constant transitions between online and offline learning formats, and heavy workloads. For students in the humanities, typical learning formats include seminar discussions, engagement with sensitive sociocultural topics, interpretative and written assignments under strict deadlines. Under such conditions, empathy — once a learning resource — may turn into a risk factor for rapid emotional exhaustion, particularly when recovery time is limited and clear evaluation procedures fail to compensate for chronic pressure and high demands.
Keywords: емоційне вигорання студентів; психологія вищої освіти